Occurrences of metamorphosed ultramafic rock and associating rocks in Howard Hills, Enderby Land, East Antarctica: Evidence of partial melting from geochemical and isotopic characteristics - Miyamoto, Tomoharu; Yoshimura, Yasutaka; Sato, Kei; Motoyoshi, Yoichi; Dunkley, Daniel J.; Carson, Christopher J. (National Institute of Polar Research, 2004)
P(論文) Large blocks of metamorphic rocks with mafic to ultramafic compositions were discovered in felsic gneiss at the central part of northern Howard Hills in Enderby Land. The ultramafic core is separated from the felsic gneiss by a mantle of pyroxene granulite. We can recognize from mineral assemblages and chemical compositions that the metamorphic rocks experienced ultrahigh temperature (UHT) metamorphism. Rubidium-strontium and samarium neodymium analytical data from the metamorphic rocks yield apparent ages of about 2.65 Ga within analytical error on isochron diagrams. Metamorphic rocks with mafic to ultramafic compositions are enriched in incompatible elements and have high Sr isotope ratios, resulting in some samples in improbable Nd model ages. This is attributed to enrichment of compatible elements and/or depletion of incompatible elements during metamorphism. We conclude that these metamorphic rocks experienced partial melting during UHT metamorphism. Pyroxene granulite was produced as a residual material after partial melting of LILE-enriched protoliths with high Sr isotope ratios. departmental bulletin paper